Peran Perawat Sebagai Fasilitator dalam Peningkatan Ekonomi Lansia - Alif, Nurhasbi; Darmiati, Darmiati (Mando Care Jurnal, 2022)
An elderly person is someone whose age undergoes biological, physical, psychological and social changes, these changes will have an influence on all aspects of life including their health. The aging process is a life cycle marked by a decrease in the function of various organs in the body which is characterized by the body's vulnerability to various diseases. One of the diseases that are often experienced by the elderly is hypertension. Therefore, the health of the elderly needs special attention, one of which is providing motivation to live by providing activities in the form of economic improvement in the form of small and medium enterprises. Nurses have an idea in realizing elderly activities in helping to optimize health and economic status, especially aimed at underprivileged elderly families and in this case nurses as facilitators introduce various products to facilitate appropriate places, introduce their products online so that the increase in business results for the elderly is seen. of the difference in sales before and after increased to 40 percent.